Comparative efficacy and safety of analgesics for acute renal colic: A network meta-analysis protocol. Issue 10 (March 2019) - Fu, Shimin; Zhang, Kebiao; Gu, Manping; Liu, Zhiping; Sun, Wenzhuo; Xiao, Mingzhao
Abstract: Introduction: Acute renal colic is one of the most common urological emergencies. While previous randomized controlled trials (RCTs) and pairwise meta-analyses only looked at the efficacy of 1 or 2 analgesics. It is not fully understood that the comprehensive ranking of the effectiveness and safeness of analgesics from these published articles. Therefore, this network meta-analysis (NMA) aims to compare and rank the different analgesics for treatment of acute renal colic. Methods and analysis: We will perform a systematic literature search in PubMed, EMBASE, CINAHL, Web of Science, and Cochrane Library to identify RCTs of different analgesics for acute renal colic. RCTs assessing active analgesics intervention against active comparator or placebo controls for acute renal colic will be included. We will also screen the reference lists of included studies, previous reviews and meta-analyses to identify other relevant trials. The primary outcomes will be pain variance at 30 minutes, need rescue medicine, complete pain relief or at least 50% pain relief at 30 minutes, and pain relapse within 24 hours. We will also assess secondary outcomes for safeness (side effects: dizziness, vomit, allergic, hypotension, cardiac toxicity, and drug dependence). The risk of bias of included RCTs will be assessed by using the Cochrane Collaboration's tool, and the quality of evidence will be assessed by using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) instrument. We will perform pairwise meta-analysis and Bayesian NMA to compare the effectiveness and safeness of different analgesic interventions. Results: This NMA will compare and rank the different analgesics for treatment of acute renal colic. Conclusion: This is the first systematic review to use the NMA to comprehensively compare and rank analgesics for relieving pain of acute renal colic in adults based on most important factors deciding the choice of initial analgesia, and the results can provide implications for clinical practice and further research. Abstract : Supplemental Digital Content is available in the text